Using the techniques of critical thinking development technology while studying economic disciplines - Sultanova, G.S. (Publ.KarSU, 2017)
The article analyzes the definition of the term «critical thinking» and specifications of the development of this type of thinking. Discusses the stages of the lesson when the technology of critical thinking development and selected strategies at some stage. At all three stages (call, understanding or realization of meaning, reflection or meditation) well-built class allows you to either increase the motivation of students to learn, or to build up their skills of independent work. All the questions posed to the students at the stage of the challenge was aimed not only at updating existing knowledge and increasing motivation for learning, including techniques of independent work. At the stage of reflection solved the main task: to teach students the ability to work independently with the scientific text. The task of the stage of reflection to integrate new knowledge into the system the available information on the subject, to develop the attitude and, if necessary, identify ways of further search on the topic. Features discussed in the article technology of critical thinking lies in the relative simplicity of its implementation in the learning process of students of economic disciplines. The practical application of the techniques of the technology of critical thinking at the lessons of economic subjects shows the development of various abilities of students.
Экономикалық пəндерді оқытуда сын тұрғысынан ойлауды дамыту технологиясы əдісін қолдану
Использование приёмов технологии развития критического мышления при изучении экономических дисциплин
Keywords: Critical Thinking Technology; characteristics and strategies of Critical Thinking; to think critically; critical thinking abilities; the process of thinking; economic disciplines